Social Rehabilitation Management For Victims Of Drugs Abuse Through Vocational Education - Khoer Mulyana, Dewi; Ulfiah; Hendi Suhendraya Muchtar; Sayid Muhammad Rifqi Noval (CV. Inara, 2022)
The problem of rehabilitation through vocational education at the Social Rehabilitation Center for Drug Abuse Victims (BRSKPN) Galih Pakuan Bogor is an unsolved problem in line with the complexity of environmental change, both in terms of implementation and evaluation, especially with regard to skill improvement. This study has a general purpose to describe, describe, and produce a hypothetical model of social rehabilitation through vocational education at BRSKPN and has a specific purpose to describe, describe, and analyze (a) planning (planning), (b) organizing (organizing), ( c) direction (command) (d) coordination (e) control (f) problems (g) solutions for social rehabilitation through vocational education. The Grand Theory in this study uses (1) the classical management theory from Henry Fayol (1841), (2) the Rehabilitation Theory from Caplin (1999) and (3) the vocational education theory from Proser (1950) and Dewey (1915). The research procedure used is a qualitative approach with a case study design. Data collection techniques were carried out by (1) Observation, (2) Interview and (3) Documentation. The results showed that (1) Social rehabilitation through vocational education at the Balai was still ineffective, (2) The coordination phase (3) The control phase at the Balai had not been effective, (4) The partnership carried out by the Balai with DUDI and the Government was still not optimal,(5 ) The demands and expectations of the community for the creation of quality vocational education in quality centers have not yet been fulfilled so that the expectations of KPN fostered children after graduation do not have the confidence and confidence to improve their vocational education, (6) The main problems faced in coordinating and controlling vocational education are: the unavailability of human resources who are specifically tasked with vocational activities, so that the learning process is not optimal, (7) solutions and anticipatory steps taken by the center in tackling HR problems or vocational instructors in collaboration with parties outside the center. The conclusion in this study shows that the social rehabilitation of vocational education in an effort to improve skills in BRSKPN is still not optimal. It is evident that only a few of the graduates have the skills. The social rehabilitation program through vocational education in the center has not been managed properly, so the learning strategies provided are not comprehensive, innovative, and creative.